Investigation of Alkali Activated Ferrochromium Slag Composites Including Waste Marble Powder - Keskinkılınç, Merve Koç; Yıldız, Servet; Eronat, Şule Sekin; Emiroğlu, Mehmet (Sakarya University, 2024)
This study investigates the potential of alkali-activated ferrochrome slag (AAFS) as a sustainable building material in combination with waste marble powder. Na2SiO3 and various molarity levels of NaOH, were evaluated to create AAFS. The study encompasses a comprehensive analysis, including SEM, XRD, and XRF, to understand the microstructure and chemical composition of the resulting composites. Consistency tests showed that an increase in molarity of the alkali activator decreased setting times, indicating that higher NaOH concentrations led to the earlier setting of the samples. XRD analysis revealed the presence of forsterite, spinel, and other crystal phases in the alkali-activated dough samples, suggesting incomplete activation of the ferrochrome slag. Higher molarity values improved compressive strength, while the inclusion of more waste marble powder reduced due to increased porosity. Additional tests, such as density measurements, capillarity experiments, and ultrasonic pulse velocity tests, provided valuable insights into the material's physical and mechanical properties. The results showed that temperature, molarity, and presence of waste marble influenced these properties. The compressive strength achievement of approximately 15 MPa at a modest temperature of 60°C during alkaline activation expresses the exceptional performance of the mixture, with marble powder utilized at the highest proportion (30%). This not only represents an energy-efficient solution but also showcases a sustainable approach that efficiently repurposes waste materials. As a result, this study demonstrates that AAFS, when properly activated and blended with waste marble powder, can yield alkali-activated composites with promising compressive strength and potential as a sustainable building material. © 2024, Sakarya University. All rights reserved.
Keywords: Alkali-activated composites; Alternative construction materials; Ferrochromium slag; Marble powder